The Evaluation of Educational Quality Management and the Way to Improve It in the College of Education for Women at the University of Baghdad from the Teachers’ Point of View (Journal Of Educational and Psychological Researches, 2023)
The research aims to examine the evaluation of educational quality management and the ways to improve it in the College of Education for Women at the University of Baghdad from the point of view of the academic staff. The research community consisted of (288) participants comprising all members of the academic staff in the College of Education for Women at the University of Baghdad for the academic year (2019-2020). As for the questionnaire, it was distributed to the academic staff of the scientific departments according to their affiliation for the purpose of identifying the availability of the requirements of the quality of the teaching service provided to them by the educational institution. The researcher adopted a questionnaire developed by the supervisory and scientific evaluation authority in the Ministry of Higher Education and Scientific Research, regarding the teacher’s satisfaction with the quality of the teaching service provided by the educational institution. The research tool consisted of two parts; the first part contains the personal information of the respondent and the second part contains (25) items with five alternatives. The results showed that the educational institution was able to achieve (16) evaluation items of requirements for the quality of service provided to the teachers, there are real difficulties represented by (9) items that made the institution itself suffer from the inability to achieve them. In light of these results, the researcher made a set of conclusions, recommendations, and suggestions.